Association between Public Reporting of Outcomes and the Use of Mechanical Circulatory Support in Patients with Cardiogenic Shock. (15th September 2019) - Singh, Vikas; Mendirichaga, Rodrigo; Bhatt, Parth; Savani, Ghanshyambhai; Jonnalagadda, Anil K.; Palacios, Igor; Cohen, Mauricio G.; O'Neill, William W.
Abstract : Risk-averse behavior has been reported among physicians and facilities treating cardiogenic shock in states with public reporting. Our objective was to evaluate if public reporting leads to a lower use of mechanical circulatory support in cardiogenic shock. We conducted a retrospective study with the use of the National Inpatient Sample from 2005 to 2011. Hospitalizations of patients ≥18 years old with a diagnosis of cardiogenic shock were included. A regional comparison was performed to identify differences between reporting and nonreporting states. The main outcome of interest was the use of mechanical circulatory support. A total of 13043 hospitalizations for cardiogenic shock were identified of which 9664 occurred in reporting and 3379 in nonreporting states (age 69.9 ± 0.4 years, 56.8% men). Use of mechanical circulatory support was 32.8% in this high-risk population. Odds of receiving mechanical circulatory support were lower (OR 0.50; 95% CI 0.43–0.57; p < 0.01 ) and in-hospital mortality higher (OR 1.19; 95% CI 1.06–1.34; p < 0.01 ) in reporting states. Use of mechanical circulatory support was also lower in the subgroup of patients with acute myocardial infarction and cardiogenic shock in reporting states (OR 0.61; 95% CI 0.51–0.72; p < 0.01 ). In conclusion, patients with cardiogenic shock in reporting states are less likely to receive mechanical circulatory support than patients in nonreporting states.